2015
DOI: 10.1177/0363546515569680
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fatty Degeneration of the Infraspinatus on the Efficacy of Arthroscopic Patch Autograft Procedure for Large to Massive Rotator Cuff Tears

Abstract: The arthroscopic fascia lata autograft patch procedure was not as beneficial for massive RCTs with high-grade fatty degeneration of the supraspinatus and infraspinatus as other treatment options that produce similar functional results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 50 publications
7
64
0
Order By: Relevance
“…However, since many studies reported that the retear rate increases with severe fatty degeneration and most massive rotator cuff tears are accompanied by chronic fatty degeneration, 3) the severity of fatty degeneration should be considered when graft is used. 23) In a study by Gupta et al, 7) the retear rate was only 20%–24% when ADP grafts were used for selected patients with low fatty degeneration. Moreover, Mori et al 8) performed rotator cuff repairs using autogenic fascia lata and reported that 8.3% of patients showed retears at the final follow-up.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, since many studies reported that the retear rate increases with severe fatty degeneration and most massive rotator cuff tears are accompanied by chronic fatty degeneration, 3) the severity of fatty degeneration should be considered when graft is used. 23) In a study by Gupta et al, 7) the retear rate was only 20%–24% when ADP grafts were used for selected patients with low fatty degeneration. Moreover, Mori et al 8) performed rotator cuff repairs using autogenic fascia lata and reported that 8.3% of patients showed retears at the final follow-up.…”
Section: Discussionmentioning
confidence: 98%
“…However, this study also included patients with grade one or two fatty degeneration in the infraspinatus according to the Goutallier classification, which was a limitation. When the same authors 23) investigated the healing failure rate in patients with high fatty degeneration, the retear rate was 89.4%, indicating that this approach was not suitable in cases with high grades of fatty degeneration. Considering the results of those studies, we think that the high healing failure rate (75%) in group II could be attributable to the fact the patients had a mean GFDI of 2.7.…”
Section: Discussionmentioning
confidence: 99%
“…76 In a cohort study, the effect of augmenting arthroscopic repairs of large to massive rotator cuff tears with a fascia lata autograft patch was evaluated, distinguishing between shoulders with low-grade and high-grade fatty infiltration. 77 Interestingly, patch augmentation was not beneficial for massive tears with highgrade fatty infiltration, 77 highlighting the importance of considering the muscle quality when applying tissue engineering strategies intended to support the healing tendonbone interface. To that end, restoring the structure and function of the degenerated muscle in the context of a chronic rotator cuff tear may further enhance the benefit of a scaffold applied to augment the surgical repair.…”
Section: Mechanical Augmentation Of the Surgical Repairmentioning
confidence: 99%
“…For instance, no benefit to augmenting repairs with a fascia lata autograft patch was found in patients with high-grade fatty infiltration of their muscles. 77 Preclinical models employing aged animals may also be of value, as older animals also experience age-associated exacerbation in muscle stiffness 241 and fatty infiltration 116 in addition to reduced healing capacity. 242…”
Section: Present Challenges and Future Perspectivesmentioning
confidence: 99%
“…Mori et al 13 reported 10.5% healing rate with fascia lata AU in a series of patients with severe fatty degeneration (Goutallier 3 or 4)49 50 of the supraspinatus and infraspinatus. However, when they evaluated a similar series of patients with severe fatty degeneration isolated to only the supraspinatus, a significantly higher healing rate (73.1%) was obtained 12.…”
Section: Discussionmentioning
confidence: 97%